EDUKASI HUKUM SIBER DAN PERLINDUNGAN DATA PRIBADI DALAM IMPLEMENTASI DIGITALISASI PEMETAAN DESA - Rommy Hardyansah; Ardica Karunia Pradana; Rio Saputra; Didit Darmawan; Agung Satryo Wibowo; Misbachul Munir; Samsul Arifin (Jurnal Pemberdayaan Masyarakat dan Inovasi, 2025)
The villages of Tambak Lekok, Jatirejo, and Tampung possess significant natural and human resources, but their utilization is still hampered by limited infrastructure and access to information. The village digitization initiative, which involves mapping using the Google Maps app, aims to improve access to information, make it easier to locate public facilities, and increase the visibility of the villages’ potential. This program employs an Asset-Based Community Development (ABCD) approach by identifying and mapping local assets through a participatory process. The results of these activities demonstrate that digital mapping can improve access to information, introduce digital technology to the community, and open up opportunities for economic development, tourism, and public services. This program is expected to serve as a first step in supporting sustainable village development based on local potential.